Dollarization of Financial Intermediation : Causes and Policy Implications - Levy Yeyati, Eduardo; Ize, Alain (Washington, D.C. : International Monetary Fund, 1998)
This paper presents a portfolio model of financial intermediation in which currency choice is determined by hedging decisions on both sides of a bank's balance sheet. Minimum variance portfolio (MVP) allocations are found to provide a natural benchmark to estimate the scope for dollarization of bank deposits and loans as a function of macroeconomic uncertainty. Dollarization hysteresis is shown to occur when the expected volatility of the inflation rate is high in relation to that of the real exchange rate. The evidence shows that MVP dollarization generally approximates actual dollarization closely for a broad sample of countries, and policy implications are explored.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet